Increasing the Added Value of Coconut Shell Waste into Briquettes - amir -; Erny Rachmawaty; Neni Damajanti (Journal of Society, Community and Business Development, 2023)
This activity aims to increase the entrepreneurial spirit of PD NA and Nasyiatul Aisyiyah members, and increase the added value of coconut shell waste into briquettes. This activity was carried out by PD and members of Nasyiatul Aisyiyah. The activity method uses an approach; 1) Entrepreneurship training with Achievement Motivation Training material, basics of entrepreneurship, business communication and marketing, 2) practice of making briquettes, 3) marketing assistance. The conclusion from this activity is that AMT training materials need to be developed further, because changing a person's mentality (mindset) to become an entrepreneur requires a process. Shell charcoal has the potential to be developed and the raw material for briquettes can be organic material, such as organic waste. Keywords: PD NA, coconut shell briquettes